2020
DOI: 10.1002/acp.3699
|View full text |Cite
|
Sign up to set email alerts
|

Successive relearning improves performance on a high‐stakes exam in a difficult biopsychology course

Abstract: Summary Successive relearning combines two effective learning techniques (retrieval practice and spaced practice) and involves practicing retrieval until some level of mastery has been reached (i.e., at least one correct retrieval attempt) in each of multiple sessions. Several laboratory studies have demonstrated the promise of successive relearning for enhancing student learning, but attempts to evaluate its effectiveness in authentic educational contexts are limited. In the current research, we implemented s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 23 publications
0
21
0
Order By: Relevance
“…If exams occur every four weeks, then a student would likely have just enough time for three (maybe four) spaced relearning sessions for any given set of material between each exam. In the investigation by Janes et al (2019) described above, this constraint was handled by cascading new materials into the SR routine as the concepts were introduced in class. One possibility is to assign the most important concepts from each class to be successively relearned in the time remaining before the next exam.…”
Section: Scheduling a Relearning Sessionmentioning
confidence: 99%
See 2 more Smart Citations
“…If exams occur every four weeks, then a student would likely have just enough time for three (maybe four) spaced relearning sessions for any given set of material between each exam. In the investigation by Janes et al (2019) described above, this constraint was handled by cascading new materials into the SR routine as the concepts were introduced in class. One possibility is to assign the most important concepts from each class to be successively relearned in the time remaining before the next exam.…”
Section: Scheduling a Relearning Sessionmentioning
confidence: 99%
“…The efficacy of SR has been demonstrated in laboratory settings using foreign-language vocabulary (e.g., chateau–castle; Bahrick, 1979; Bahrick, Bahrick, Bahrick, & Bahrick, 1993; Rawson et al, 2018; Vaughn, Dunlosky, & Rawson, 2016) and key-term definitions (e.g., Rawson & Dunlosky, 2011, 2013). Even more critical, its efficacy has also been tested in authentic classrooms, including an introductory psychology course (Rawson, Dunlosky, & Sciartelli, 2013) and a biopsychology course (Janes, Dunlosky, Rawson, & Jasnow, 2019). For the former, performance on a high-stakes exam was over 10% better on questions that tapped definitions learned by SR than by business as usual.…”
Section: Evidence For the Efficacy Of Successive Relearningmentioning
confidence: 99%
See 1 more Smart Citation
“…Since this first evaluation of SR in a classroom setting, it was shown to improve students’ performance on an in-class exam in biopsychology (Janes et al, 2020) and their retention of key terms in another introductory psychology course (Higham et al, 2021). In the latter case, students’ use of SR across a semester also decreased their reported anxiety about using it (as compared with restudying the key terms, i.e., using their usual study methods) and led them to realize that SR was a more effective approach to learning than is restudying (Higham et al, 2021).…”
Section: Efficacy Of Successive Relearning In Promoting Retentionmentioning
confidence: 99%
“…A small evidence base suggests that successive relearning produces excellent and durable memory for learned material—more than either single-session testing or spaced practice on its own (e.g., Bahrick, 1979; Bahrick et al, 1993; Bahrick & Hall, 2005; Janes et al, 2020; Rawson & Dunlosky, 2011, 2012, 2013; Rawson et al, 2013; Vaughn et al, 2016). For example, Rawson et al (2018) found that participants recalled 20% of learned information one week after a single learning session.…”
Section: Successive Relearningmentioning
confidence: 99%